(untitled) - Nise, Norman S (London, 2004)
Designed to make the material easy to understand, this clear and thorough book emphasizes the practical application of systems engineering to the design and analysis of feedback systems. Nise applies control systems theory and concepts to current real-world problems, showing readers how to build control systems that can support today's advanced technolog
Keywords: Automatic control,Systems engineering